2016
DOI: 10.1007/s10792-016-0276-6
|View full text |Cite
|
Sign up to set email alerts
|

Inner retinal thinning after Brilliant Blue G-assisted internal limiting membrane peeling for vitreoretinal interface disorders

Abstract: The aim of this study was to evaluate ganglion cell layer and nerve fiber layer thickness after Brilliant Blue G (BBG)-assisted internal limiting membrane (ILM) peeling for vitreomacular disorders. Retrospective analysis of spectral domain optical coherence tomography (SD-OCT) of 42 eyes of 42 patients, who underwent pars plana vitrectomy with BBG-assisted ILM peeling, was performed. Inclusion criteria were idiopathic macular hole, idiopathic vitreomacular traction, and idiopathic epiretinal membrane. Key excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…The substantial equivalence of the two groups with regard to the parafoveal macular area thickness (MT), which includes all the neural retina layers, and the inner 3-mm parafoveal area including ILM, GCL++ seems to deny difference in toxicity from the two dyes by SS-OCT evaluation at this level. The thinning of the outer 6-mm GCL++ area from 6 to 12 months in all sectors in both groups is in agreement with literature data, since, as described in the introduction, thinning of the inner retina, including GCL++ and RNFL, after ILM peeling has been described both with ICG and BBG in SD-OCT-based studies [24,[30][31][32][33]. In our patients, we must at first note that in the majority of cases, as described in the surgical procedure section, ILM surgical manipulation began near the inferior or superior vascular arcade.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The substantial equivalence of the two groups with regard to the parafoveal macular area thickness (MT), which includes all the neural retina layers, and the inner 3-mm parafoveal area including ILM, GCL++ seems to deny difference in toxicity from the two dyes by SS-OCT evaluation at this level. The thinning of the outer 6-mm GCL++ area from 6 to 12 months in all sectors in both groups is in agreement with literature data, since, as described in the introduction, thinning of the inner retina, including GCL++ and RNFL, after ILM peeling has been described both with ICG and BBG in SD-OCT-based studies [24,[30][31][32][33]. In our patients, we must at first note that in the majority of cases, as described in the surgical procedure section, ILM surgical manipulation began near the inferior or superior vascular arcade.…”
Section: Discussionsupporting
confidence: 91%
“…Optical coherence tomography (OCT) analysis of central foveal thickness (CFT) and length of the defect of the photoreceptor inner segment/outer segment junction (IS/OS) indicate better outcomes with BBG than ICG in traditional FTMH surgery [29]. However, some experimental and clinical studies indicate a degree of toxicity from blue dyes in vitreoretinal interface and traditional macular hole surgery [24,[30][31][32]. Studies using spectral-domain (SD) OCT analysis point out postoperative thinning of the inner retinal layers after BBG-stained ILM peeling, mainly of the temporal macular ganglion cell and inner plexiform layer (GCL++) [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study including 42 eyes, significant decreases were observed in mean GCIPL thickness and superior sector GCIPL thickness at postoperative 3 and 6 months after ILM peeling with brilliant blue G compared to baseline values, and it was found that this thinning was also accompanied by RNFL thinning. 37 …”
Section: Discussionmentioning
confidence: 99%
“…İnsan pigment epitel hücrelerinde elektrofizyolojik değerlendirmeler 5 dakikalık boya uygulaması ile retina gangliyon hücreleri üzerinde toksik etki olmadığını göstermiştir. [52] Retrospektif karşılaştırmalı bir vaka serisinde Membran Blue Dual ile başarılı cerrahi sonuçlar bildirilmiştir. [53] İç Limitan Membrana Yönelik Farklı Cerrahi Yöntemler İLM soyulmasının klinik sonuçları tam bilinmemekle beraber, takipler sırasında progresif optik sinir lifi tabakası ayrışması, papillomaküler mesafede kısalma ve makulanın asimetrik yer değiştirmesi gibi anatomik değişiklikler kaydedilmiştir.…”
Section: İdiyopatik Makula Deliğinde İç Limitan Membran Soyulmasının Rolüunclassified